Improving the Quality of High Density Polyethylene Pipes using Design of Experiments - Assaf, Ramiz; Haddad, Tamer; Kanan, Mohammed (International Journal of Engineering and Technology, 2019)
The purpose of this work is to study quality related problems in polyethylene pipe products and to improve their quality. Design of Experiment methodology will be used in order to ï¬nd the optimum settings of the production processes parameters and to reduce the defects.Â Based on data collected and after the analysis the signiï¬cant factor is haul off speed, interaction between screw speed and temperature andÂ interaction between screw speed and haul off speed. The results show that the optimum run was operating at high level off haul of speed andlow level of screw speed and temperature, this run most of the samples that produced are match to the customersâ€™ speciï¬cation.